QUETIAPINE ADD-ON THERAPY MAY IMPROVE PERSISTENT SLEEP DISTURBANCES IN PATIENTS WITH PTSD ON STABILE COMBINED SSRI AND BENZODIAZEPINE COMBINATION: A ONE-GROUP PRETEST-POSTTEST STUDY - Vilibic, Maja; Peitl, Vjekoslav; Zivkovic, Maja; Vlatkovic, Suzana; Ljubicic Bistrovic, Ivana; Ljubicic, Rudolf; Matosic, Ana; Karlovic, Dalibor (Psychiatria Danubina, 2022)
To assess potential benefits of quetiapine for persistent sleep disturbances in patients with posttraumatic stress disorder (PTSD) on stable combined SSRI and benzodiazepine therapy, who previously failed to respond to various benzodiazepine and non-benzodiazepine hypnotic adjuvant treatment as well as to first-generation antipsychotic add-on treatment.BACKGROUNDTo assess potential benefits of quetiapine for persistent sleep disturbances in patients with posttraumatic stress disorder (PTSD) on stable combined SSRI and benzodiazepine therapy, who previously failed to respond to various benzodiazepine and non-benzodiazepine hypnotic adjuvant treatment as well as to first-generation antipsychotic add-on treatment.Fifty-two male PTSD outpatients on stable combination treatment with SSRI and benzodiazepines, with persistent sleep disturbances not responding to prescription of zolpidem, flurazepam, nitrazepam, promazine, and levopromazine, were assessed for sleep disturbances improvements after prescription of quetiapine in the evening. Each patient met both ICD-10 and DSM-IV criteria for PTSD. Psychiatric comorbidity and premorbidity were excluded using the Mini-International Neuropsychiatric Interview (MINI). Improvement on the CAPS recurrent distressing dream item, reduction in the amount of time needed to fall asleep, prolongation of sleep duration, and reduction in average number of arousals per night in the last 7 days before the assessment period were used as efficacy measures.SUBJECTS AND METHODSFifty-two male PTSD outpatients on stable combination treatment with SSRI and benzodiazepines, with persistent sleep disturbances not responding to prescription of zolpidem, flurazepam, nitrazepam, promazine, and levopromazine, were assessed for sleep disturbances improvements after prescription of quetiapine in the evening. Each patient met both ICD-10 and DSM-IV criteria for PTSD. Psychiatric comorbidity and premorbidity were excluded using the Mini-International Neuropsychiatric Interview (MINI). Improvement on the CAPS recurrent distressing dream item, reduction in the amount of time needed to fall asleep, prolongation of sleep duration, and reduction in average number of arousals per night in the last 7 days before the assessment period were used as efficacy measures.All sleep-related parameters improved significantly at the end of a five-week follow-up: sleep duration increased by one hour (p<0.001), sleep latency decreased by 52.5 minutes (p<0.001), median number of arousals per night decreased from two to one (p<0.001), CAPS recurrent distressing dream item median decreased from five to four (p<0.001), and the number of patients dissatisfied with their sleep quality and quantity decreased from 45 to two (p<0.001).RESULTSAll sleep-related parameters improved significantly at the end of a five-week follow-up: sleep duration increased by one hour (p<0.001), sleep latency decreased by 52.5 minutes (p<0.001), median number of arousals per night decreased from two to one (p<0.001), CAPS recurrent distressing dream item median decreased from five to four (p<0.001), and the number of patients dissatisfied with their sleep quality and quantity decreased from 45 to two (p<0.001).Quetiapine prescribed in the evening may be successful therapy for persistent sleep disturbances in patients with PTSD and generally good response to an SSRI and benzodiazepine combination, who previously failed to respond to some of the usual hypnotic medication or addition of first-generation antipsychotics: zolpidem, flurazepam, nitrazepam, promazine, and levopromazine.CONCLUSIONQuetiapine prescribed in the evening may be successful therapy for persistent sleep disturbances in patients with PTSD and generally good response to an SSRI and benzodiazepine combination, who previously failed to respond to some of the usual hypnotic medication or addition of first-generation antipsychotics: zolpidem, flurazepam, nitrazepam, promazine, and levopromazine.